Cultures of America Irish Americans - Riehecky, Janet (Marshall Cavendish Corporation, 1995)
Looks at Ireland and the reasons why people left to come to the United States; explores life in America, the importance of family and religion, and types of music, celebrations, art, food, and customs; and examines contributions made by Irish Americans
Keywords: Juvenile Nonfiction; Other; People & Places; United States